2005
DOI: 10.1097/01.ftd.0000159134.94981.3f
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Study Between Enoxacin and Fluvoxamine

Abstract: Authors examined a possible interaction between enoxacin, an inhibitor of cytochrome P4501A2, and fluvoxamine (FLV), a substrate for this enzyme. Ten healthy male volunteers received enoxacin 200 mg/d or placebo for 11 days in a double-blind randomized crossover manner, and on the eighth day they received a single oral 50-mg dose of FLV. Blood samplings and pharmacodynamic evaluation were conducted up to 72 hours after FLV dosing. Plasma concentrations of FLV and its active metabolite fluvoxamino acid (FLA) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The results of previous studies indicate that CTXA may alter the metabolism of CYP1A2. Enoxacin and fluvoxamine are strong inhibitors of CYP1A2, and their activities were previously reported in an in vivo drug-interaction, where enoxacin was an inhibitor of CYP1A2 and fluvoxamine was a substrate (Kunii et al, 2005). Decursin, used as a traditional Asian medicine for examining the pharmacokinetics of theophylline in rats, is a typical substrate of CYP1A2 enzyme (Chae et al, 2012).…”
Section: Resultsmentioning
confidence: 97%
“…The results of previous studies indicate that CTXA may alter the metabolism of CYP1A2. Enoxacin and fluvoxamine are strong inhibitors of CYP1A2, and their activities were previously reported in an in vivo drug-interaction, where enoxacin was an inhibitor of CYP1A2 and fluvoxamine was a substrate (Kunii et al, 2005). Decursin, used as a traditional Asian medicine for examining the pharmacokinetics of theophylline in rats, is a typical substrate of CYP1A2 enzyme (Chae et al, 2012).…”
Section: Resultsmentioning
confidence: 97%
“…25 Therefore, the present results are almost in accordance with this pharmacokinetic principle, and suggest that caffeine slightly induces the metabolism of FLV. This induction is probably mediated by CYP1A2, because this enzyme is involved in FLV metabolism 5,6,8 and inducible by caffeine intake. 23,24 The specific metabolic pathway(s) of FLV induced by caffeine remains unclear, but the demethylation to FLA does not seem to be involved, because the pharmacokinetic parameters of FLA including the AUC-ratio of FLA to FLV were not significantly different between the 2 phases.…”
Section: Discussionmentioning
confidence: 97%
“…Scores from 0.5 to 4 h postdose were significantly higher (i.e. patients were more sleepy) during enoxacin coadministration compared with placebo coadministration (p < 0.05) [273]. A single-dose trial evaluating the effect of ciprofloxacin on sildenafil pharmacokinetics found that ciprofloxacin coadministration resulted in significant increases in t½ (mean 38%), AUC (mean 112%) and C max (mean 117%) (all p < 0.05).…”
Section: Metabolism Interactionsmentioning
confidence: 95%